Clear and Understandable Language as a Guarantee for Access to Justice in Peru - Tello Gilardi, Janet Ofelia Lourdes (2025)
The article addresses the relevance of clear and simple language as an essential tool to ensure accessible and understandable justice for all, as it fosters equality and trust in the judicial system. Equal justice is a fundamental principle that guarantees equal rights and opportunities in access to justice, particularly for individuals and groups in situations of vulnerability. Likewise, the study demonstrates the importance of clear language in the field of justice as part of the commitment of the Judiciary of Peru to implement the 100 Brasilia Rules, especially Rule 58, according to which every person in a situation of vulnerability has the right to understand and be understood; therefore, the necessary measures must be adopted to reduce communication barriers that hinder the understanding of judicial proceedings, in pursuit of comprehensible, sensitive justice adapted to the needs of less favored sectors.